2014
DOI: 10.4291/wjgp.v5.i4.392
|View full text |Cite
|
Sign up to set email alerts
|

Treatment ofHelicobacter pyloriinfection: Past, present and future

Abstract: Helicobacter pylori (H. pylori) is a major human pathogen associated with significant morbidity and mortality. However, after decades of efforts, treatment of H. pylori remains a challenge for physicians, as there is no universally effective regimen. Due to the rising prevalence of antimicrobial resistance, mainly to clarithromycin, efficacy of standard triple therapies has declined to unacceptably low levels in most parts of the world. Novel regimens, specifically experimented to improve the therapeutic outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 82 publications
0
76
0
1
Order By: Relevance
“…Modifications in the rdxA gene, assumed to be point mutations, are considered a primary cause [30] . Metronidazole resistance may also influence the treatment outcome, although it is generally considered less clinically important than clarithromycin resistance [52,53] . Overall, the Eastern Asian region has higher metronidazole resistance rates with 95.4% in the southeast coastal region of China [39] and 71.3% in Japan [37] .…”
Section: Current Antibiotic Resistance In Worldwidementioning
confidence: 99%
See 2 more Smart Citations
“…Modifications in the rdxA gene, assumed to be point mutations, are considered a primary cause [30] . Metronidazole resistance may also influence the treatment outcome, although it is generally considered less clinically important than clarithromycin resistance [52,53] . Overall, the Eastern Asian region has higher metronidazole resistance rates with 95.4% in the southeast coastal region of China [39] and 71.3% in Japan [37] .…”
Section: Current Antibiotic Resistance In Worldwidementioning
confidence: 99%
“…Bismuth quadruple therapy (bismuth subcitrate potassium, metronidazole, tetracycline, PPI) has been suggested as a first-line treatment option for regions with a high (> 20%) incidence of clarithromycin resistance [53] .…”
Section: Publication Treatment Duration Patients Therapy Regimen Eradmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard regimen such as clarithromycin plus proton pump inhibitor (PPI) plus amoxicillin or metronidazole for 7, 10 and 14 days is worldwide followed by first-line treatment regimen. It has revealed that PPI-based triple regimen which provided eradication rates greater than 80-90%, usually consisting of a PPI, amoxicillin, and clarithromycin (Papastergiou et al, 2014). The recent national survey reported that the eradication rate of triple therapy, which is 84.92-87.50% from 2001 to 2007, but 80-81.43% from 2008 to 2010 (Sherief et al, 2016).Review studies have shown that eradication rate is highest using amoxicillin with PPI and clarithromycin (83.50%) than metronidazole 68.64% as well as PPI, amoxicillin, and metronidazole the rate 82%; each therapy lasting 14 days (Ermis et al, 2015).…”
Section: First-line Therapymentioning
confidence: 99%
“…But standard triple therapy has been recently declined efficacy due to antibiotic resistance resulting decreased eradication rates. Bismuth quadruple, concomitant, sequential and levofloxacin therapies are currently better than standard therapy that is providing promoted efficacy (Ermis et al, 2015;Papastergiou et al, 2014;Benjamin et al, 2010). Therefore, this study major purposed to provide a reconsideration modern beneficial efficacy of the drug and better eradication rates of H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%